Kalvningsintervall hos svenska köttkor : finns det genetisk variation som kan användas i avelsarbetet? - Lennartsson, Maria (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2008)
The Swedish beef cattle population is growing when the dairy cattle become fewer. The fertility of the beef cows is important for the profitability in beef cattle production. Today there is no genetic evaluation for female fertility in Swedish beef cows. The purpose of this study was to see if calving interval can be used in the genetic evaluation as a measure of female fertility in beef cows. For this purpose the variation in calving interval for beef cows of different breeds and ages registred in KAP was studied. Genetic parameters were calculated for charolais and hereford. Data from Svensk Mjölk were used. In the analyses purebred cows that calved between the years 1987 and 2005 were included.